La fête du Santo Cristo à Montréal: histoire, idéologie et mentalité du peuple portugais - Araujo, Antonio (Université de Montréal, 1991)
Keywords: Portugais

Origines, richesse et travail / Origins, Wealth and Work - Fyson, Donald; Young, Brian (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: Irlandais; McCord (famille)

Rononshonni - le Bâtisseur. La collection McCord d'objets ethnographiques - McCaffrey, Moira T. (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: McCord; David Ross; Musée McCord; Musées

Historiography, Myth and Group Relations: Jewish and Non-Jewish Québécois on Jews and New France - Menkis, Richard (Canadian Ethnic Studies / Études ethniques au Canada, 1991)
Number: 2
Keywords: Histoire; Juifs

Histoire et histoires dans la métropole québécoise: le quartier Côte-des-Neiges - Ramirez, Bruno (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

L'immigration belge au Canada: une histoire en devenir - Jaumain, Serge; Sanfilippo, Matteo (Les immigrants préférés: Les Belges, 1999)
Keywords: Belges

Le fascisme et les Italiens à Montréal: une histoire orale, 1922-1945 - Salvatore, Filippo (Guernica, 1995)
Keywords: Idéologies; Italiens

Tur Malka: flâneries sur les cimes de l'histoire juive montréalaise - Anctil, Pierre (Septentrion, 1997)
Keywords: Juifs

Sujets et identités multiples: analyse des histoires de vie d'un groupe d'immigrants italiens à Montréal - Peressini, Mauro (Université de Montréal, 1991)
Keywords: Italiens

Une quête identitaire entre mythe et histoire: les Juifs ashkénazes à l'aventure de l'Amérique en Québec - Barriault, Lise (Université du Québec à Montréal, 1998)
Keywords: Juifs

Le dictionnaire de bon langage d'Étienne Blanchard: étude métalexicographique; contribution à l'histoire de la lexicographie québécoise - Prévost, Geneviève (Université Laval, 1996)
Keywords: Linguistique

Les mécanismes privés d'accueil et d'assistance aux immigrants. Une étude de cas: la Société d'assistance aux immigrants, 1950-1957 - Lévesque, Edna (Université du Québec à Montréal, 1991)
Keywords: Société d'assistance aux immigrants

La société canadienne-française et le théâtre lyrique à Montréal entre 1840 et 1913 - Barrière, Mireille (Université Laval, 1990)
Keywords: Francophones; Théâtre

Hometown and Family Ties: The Lebanese-Syrians of Montreal, 1905-1950 - Moser, Diane (Université McGill, 1990)
Keywords: Libanais; Syriens

La reconquête de Montréal - Levine, Marc V. (VLB Éditeur, 1997)
Keywords: Anglophones; Francophones

Pour en finir avec un mythe: le refus des écoles catholiques d'accepter les immigrants - Gagnon, Robert (Bulletin d'histoire politique, 1997)
issued: 1997-24-00
Keywords: Commission des écoles catholiques de Montréal

Représentation et rôle des Québécois / Canadiens français dans le radioroman de guerre 1939-1945 - Legris, Renée (Bulletin d'histoire politique, 1995)
issued: 1995-21-00/1995-22-00
Keywords: Guerre; Radio; Roman

L'unilinguisme français et le projet souverainiste du Parti québécois vus par la communauté juive du Québec (1974-1981) - Cloutier, Caroline (Bulletin d'histoire politique, 1999)
issued: 1999-23-00
Keywords: Juifs; Langue; Nationalisme; Partis politiques

Montreal of Yesterday: A Snapshot of Jewish Life in Montreal During the Era of Mass Immigration - M. Baker, Zachary (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Medres; Israel Jonah

Genèse d'une communauté lesbienne: un récit des années 1970 - Hildebran, Andrea (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Anglophones; Femmes; Francophones

Immigration et communautés ethno-culturelles - Taschereau, Sylvie (Guide d'histoire du Québec: du régime français à nos jours: bibliographie commentée, 1991)

The Senator, The Merchant, Two Carpenters and a Widow: A Survey of Canadian Landlords in 1871 - Burley, David G. (Urban History Review / Revue d'histoire urbaine, 1997)
Number: 2
Keywords: Logement

Entente cordiale? La section montréalaise du Fonds patriotique canadien, 1914-1923: le bénévolat de guerre à Montréal - Morton, Desmond (Revue d'histoire de l'Amérique française, 1999)
issued: 1999-23-00
Keywords: Bénévolat; Guerre

Ethnicity and Home Ownership in Montreal, 1921–51 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1998)
Number: 2
Keywords: Locataires; Logement

Le «boom» des immeubles d’appartements à Montréal de 1921-1951 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1994)
Number: 1
Keywords: Logement; Outremont; Westmount

Le comportement électoral des minorités au Québec lors des élections de 1976 - Jedwab, Jack (Bulletin de l'association québécoise d'histoire politique, 1994)
issued: 1994-21-00
Keywords: Anglophones; Élections

The Saint Patrick's Society of Montreal: Ethno-Religious Realignment in a Nineteenth-Century National Society - James, Kevin (Université McGill, 1997)
Keywords: Irlandais

The Jackie Robinson Myth: Social Mobility and Race in Montreal, 1920-1960 - Williams, Dorothy W. (Université Concordia, 1999)
Keywords: Enseignants; Lord; Gwen; Lord; Richard; Noirs; Robinson; Jackie

The Ideological and Intellectual Baggage of Three Fragments of Ukrainian Immigrants: a Contribution to the History of the Ukrainians in Quebec (1910-1960) - Kelebay, Yarema Gregory (Université Concordia, 1992)
Keywords: Idéologies; Ukrainiens

The Antiochan Orthodox Syrians of Montreal 1905-1980: an Historical Study of Cultural and Social Change Over Three Generations - Marino, Norman (Université Concordia, 1994)
Keywords: Syriens

Les organisations féminines de la communauté juive montréalaise, 1918-1948 - Filotas, Sarah (Université de Montréal, 1998)
Keywords: Femmes; Juifs

Omer Héroux and La Vérité, 1904-1908: French-Canadian Nationalism and Catholicism in the Early Twentieth Century - Morrison, H. Jean (Université Concordia, 1992)
Keywords: Nationalisme; Écrivains

A Foothold in the Whirlpool: Canada's Iberian Refugee Movement - Reed, Patrick (Université Concordia, 1996)
Keywords: Juifs

La famille juive à Montréal au tournant du XXe siècle - Soucy, Isabelle (Université du Québec à Montréal, 1999)
Keywords: Famille; Juifs

Les Franco-Américains à Montréal au début du XXe siècle - Rodrigue, Martine (Université du Québec à Montréal, 1997)
Keywords: Américains; Francophones

Différenciation sociale et rituels du mariage: les Montréalais francophones, 1925-1940 - Girard, Denise (Université Laval, 1998)
Keywords: Francophones; Mariage

Les immigrants français à Montréal, 1850-1901. Étude des Français présents à Montréal lors du recensement de 1901 - Filot, Ingrid (Université Lumière Lyon 2, 1995)
Keywords: Français

Community and Identity in Nineteenth Century Montreal: The Founding of Saint Patrick's Church - Leitch, Gillian I. (Université d'Ottawa, 1999)
Keywords: Irlandais; St. Patrick (église); Églises

Les communautés protestantes francophones au Québec, 1834-1925 - Vogt-Raguy, Dominique (Université Michel de Montaigne-Bordeaux 3, 1996)
Keywords: Francophones; Protestants

Les organisations de solidarité avec le Chili à Montréal, 1973-1993 - Hervas Segovia, Epiganio Roberto (Université du Québec à Montréal, 1997)
Keywords: Chiliens

L'immigration française au Canada de 1945 à 1960 - Leblond, Francis (Université Laval, 1993)
Keywords: Français

Le sport chez les Canadiens-français de Montréal au XIXe siècle - Janson, Gilles (Université du Québec à Montréal, 1993)
Keywords: Baseball; Crosse; Football; Palestre nationale; Raquetteurs

Afro-Canadian Activism in the 1960s - Stamadianos, Peter (Université Concordia, 1994)
Afro-Canadian activism became increasingly militant in the 1960s. The rise in militancy in the Afro-American leadership of the 1960s was one factor contributing to the new era of black politics in Canada. Increased immigration from the West Indies also encouraged the proliferation of Afro-Canadian organizations dedicated to challenging racial discrimination. Afro-Canadian activism, however, developed in a substantially different manner than black politics in the United States. On the whole, most Afro-Canadian organizations and leaders were considerably less militant in their tactics and strategies than their counterparts in the United States. Internecine divisions over ancestral origin were also more pronounced in Canada where the black population was ethnically heterogeneous when compared to the Afro-American community.
Keywords: Africains; Noirs

Montreal's Scottish Community, 1835-65: A Preliminary Study - McNabb, Heather (Université Concordia, 1999)
Keywords: Écossais

Writing Bodies: Modern Dance, Gender, and Jewish Identity in New York and Montreal, 1930 to 1960 - Hardt, Yvonne (Université Concordia, 1999)
Keywords: Danse; Juifs

Constructing Italian Ethnicity: A Comparative Study of Two Italian Language Newspapers in Australia and Canada, 1947-1957 - Iuliano, Susanna (Université McGill, 1994)
Keywords: Italiens

Gender, Race, and Power: the Chinese in Canada, 1920-1950 - Huang, Belinda (Université McGill, 1998)
Keywords: Chinois

Expulsion des immigrants indésirables à Montréal: 1911-1914 - Legeay, Guilaine (Université d'Angers, 1999)

Le monde du travail comme moyen d'intégration des Portugais au Québec (1953-1995): ou comment marier le vieux et le neuf - Lopes, Duarte (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1995)
issued: 1995-22-00
Keywords: Portugais

Montréal. Une société multiculturelle - McNicoll, Claire (Belin, 1993)
Keywords: Mobilité résidentielle

Le monument inattendu, le Monument-National, 1893-1993 - Larrue, Jean-Marc (Hurtubise HMH, 1993)
Keywords: Société Saint-Jean-Baptiste; Théâtre; École nationale de théâtre du Canada

The Kosher Meat War and the Jewish Community Council of Montreal, 1922-1925 - Robinson, Ira (Canadian Ethnic Studies / Études ethniques au Canada, 1990)
Number: 2
Keywords: Alimentation; Cohen; Hirsch; Juifs; Rosenberg; Yudel

Ethnic Strategies in the Urban Economy - Olson, Sherry (Canadian Ethnic Studies / Études ethniques au Canada, 1991)
Number: 2
Keywords: Travail

Modes d'acculturation et d'identité située: Le cas des immigrants haïtiens de Montréal - Clément, Richard; Sylvestre, André; Noels, Kimberly (Canadian Ethnic Studies / Études ethniques au Canada, 1991)
Number: 2
Keywords: Haïtiens

The Reconquest of Montreal. Language Policy and Social Change in a Bilingual City - Levine, Marc V. (Temple University Press, 1990)
Keywords: Anglophones; Francophones

La tunique aux couleurs multiples. Deux siècles de présence juive au Canada - Abella, Irving (Musée canadien des Civilisations, 1990)
Keywords: Juifs

A Coat of Many Colours. Two Centuries of Jewish Life in Canada - Abella, Irving (Lester and Orpen Dennys, 1990)
Keywords: Juifs

The Segregated City: Class Residential Patterns and the Development of Industrial Districts in Montreal 1861 and 1901 - Lewis, Robert D. (Journal of Urban History, 1991)
Number: 2
Keywords: Locataires; Logement; Mobilité résidentielle

La perception de la qualité de la langue au Québec de 1960 à 1992 d'après les opinions publiées dans La Presse - Lajeunesse, Lyse (Université de Sherbrooke, 1997)
Keywords: Langue; Presse (La)